Global Justice: Why not State jurisdictions in transnational financial disputes? - Manzo, Alejandro Gabriel (2019)
The article brings the debate about Global Justice to the centre stage of the Sovereign Debt Restructuring (SDRs) field. The judicial system that intervenes in sovereign debt conflicts was not on the agenda of the last reform processes activated in this field. In the NML Capital vs. Argentina (NML) trial, judges from different instances and different jurisdictions issued declarations of the same dimensions related to the same object of litigation. The article makes a comparative analysis of the argumentative strategies that judges used at the time of justifying their positions in order to show the tensions in which they incurred. It is explained that: a) these tensions are the result of agents –the judges– that must take decisions in a context of crossroads where the expected option in accordance with usual legal practices would undermine their own position in the field of sovereign debt market; b) these crossroads are rooted in the structural limits of the judicial system in which these agents operate. Contrary to what official statements postulate, it is argued that these limits conspire against the possibility that state courts provide Justice in transnational disputes, in which they must judge another equally sovereign State.